An Untapped Resource: Patient and Public Involvement in Implementation; Comment on "Knowledge Mobilization in Healthcare Organizations: A View From the Resource-Based View of the Firm" - Christopher Burton; Jo Rycroft-Malone (Kerman University of Medical Sciences, 2015)
This commentary considers the potential role of patient and public involvement in implementation. Developing an analytical thread from the resource-based view of the Firm, we argue that this involvement may create unique resources that have the capacity to enhance the impact of implementation activity for healthcare organisations.